The multi-sourcing journey of a European retailer: A roller coaster ride or smooth sailing?. Issue 1 (May 2020) - Plugge, Albert
During the last decade, the scope of IT outsourcing arrangements evolved from a dyadic client–vendor relationship to a multi-sourcing environment characterized by sourcing inter-dependent services from multiple vendors. This case study addresses the journey of a large client firm in the retail sector who experienced that managing a multi-sourcing arrangement differs significantly from managing bilateral (i.e. dyadic) relationships. The journey consists of three phases: the initiation phase (2008–2010), which can be characterized as stressful and intense; the adaption phase (2010–2012); and the stabilization phase (2012–2015). The case describes actual situations along the journey, including the client's previous experience, the deal making, the challenges and conflicts faced by the client and their vendors, and the strategic change toward a collaborative type of multi-sourcing arrangement.